Pengembangan Gim Edukasi “Smart Flowers” untuk Pengenalan Bunga Berbasis Android - Andrew Christian Thuwijaya; Yulia Ery Kurniawati (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
This study aims to develop an interactive educational game for learning about flowers. This game is specifically for elementary school students due to their lack of knowledge and limited means to learn about flowers. The development of this game uses the Game Development Life Cycle method and Unity Engine software. The result of this study is an Android-based educational game,